Freer markets, more rules : - Vogel, Steven K. (Cornell University Press, 1996)
Vogel writes with extraordinary clarity about a very complex subject. His discussion of deregulation in Japan not only gives the reader a clear understanding of the distinct issues of market liberalization and regulatory reform as they have been pursued in Japan, but also offers a nuanced analysis of the relationship between state and market in contemporary Japan